DEVELOPMENT OF TI/PBO2/ SB2O3 ELECTRODE AS INDICATOR ELECTRODE FOR PH MEASUREMENTS AND CONDUCTOMETRIC TITRATIONS IN AQUEOUS SOLUTIONS - MAZEN HAMADA (International Journal of Pharma and Bio Sciences, 2014)
Ti/PbO2/Sb2O3 electrode was used as indicator electrode in potentiometric and conductometric titration in aqueous solution at 298 K. The E-pH curve is linear with a slope of 0.0505 V/dec at 298 K which is close to the theoretical value 2.303RT/F (0.059 V at 298 K). The standard potential of this electrode, E0, is computed with respect to the SCE as reference electrode. The recovery percentages for potentiometric and conductometric titration are calculated. The cell constant for this conductometric cell was determined. The specific conductance for standard KCl was determined and compared with that of glass conductivity cell. The variation of molar conductance with dilution for some common electrolytes was tested as well as the molar conductance at infinite dilution of some common electrolytes is determined by the conductive cell and conductive glass cell. The prepared modified electrode was used in potentiometric and conductometric titrations for H3PO4 and HCl respectively against NaOH as titrant in aqueous medium at 298 K.